Capacity Building of Accounting Teachers in Integrated Reporting to Support Junior Accountant Competency - Wiwik Utami; Eliyani Eliyani; Rieke Pernamasari; Abdul Hadi Zulkafli; Supriyadi Supriyadi; Aditya Handi Chandra; Naily Syahfitri (Universitas Malahayati Lampung, 2026)
ABSTRACT This community service program aims to strengthen the capacity of members of the Accounting Teacher Working Group (MGMP) of Tangerang City in teaching the concepts of green accounting, sustainability reporting, and the green economy. The activity was carried out using a Participatory Action Research (PAR) approach combined with a community-service model through three stages: needs analysis, a one-day intensive training session, and program evaluation. The training was attended by 50 SMK Accounting teachers from Tangerang City, Banten, delivered through lectures, contextual case studies of companies in Indonesia, and interactive discussion covering three main topics: green accounting, sustainability reporting frameworks, and the concept of the green economy. The program was evaluated using a structured questionnaire completed by all participants and activity partners. The evaluation results show that participant agreement (combining the